Examination of Perceived Stress Levels of Individuals Who Attending University Education and Participate in University Team - Ünal Türkçapar; Murat Atasoy (Selcuk University, 2023)
Abstract Aim: This study is to determine how the perceived stress levels of individuals who play individual and team sports in university teams are shaped. Method: Scanning method was used in this study. This study has a descriptive and inferential nature. The study was carried out with 159 individuals in the school teams of Kyrgyzstan-Turkey Manas University in the 2021-2022 academic year. The study was shaped on the basis of voluntary participation criteria. In this study, demographic information form prepared by the researcher and Perceived Stress Scale were used to collect data. The obtained data were transferred to computer environment and evaluated with SPSS 25.0 statistical program. By using parametric tests on the data, t-test was used for pairwise group comparisons, ANOVA test was applied for comparing more than two groups, and Post Hoc Turkey multiple comparison test was applied to determine the difference between groups. Findings: In shaping the perceived stress levels of university students; according to the gender variable, women have a higher average than men, according to the age variable, there is a difference in favor of the older ones, according to the type of sport variable in favor of the team sports, according to the competition success variable in favor of the international participants and according to the income level variable, there is a difference in favor of the weak ones but it was concluded that there was no significant difference according to the sports year variable. Conclusion: It was concluded that gender is of great importance in the perceived stress levels of individuals studying at university and participating in school teams.